2013
DOI: 10.2478/s11756-013-0247-6
|View full text |Cite
|
Sign up to set email alerts
|

Ongoing succession of biological soil crusts increases water repellency — a case study on Arenosols in Sekule, Slovakia

Abstract: After soil surface disturbances biological soil crusts (BSC) cover rapidly the topmost soil millimeters. Depending on BSC age, development of soil water repellency, water infiltration and soil surface stability are influenced by this thin surface sealing. Within this study disturbed, early-mid-and late successional stages of BSC development were examined along a recovery transect. The results show an increase in water repellency and a decrease in water sorptivity and conductivity with ongoing BSC succession. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 24 publications
3
21
0
Order By: Relevance
“…This agrees with Eldridge et al (2010), Maestre et al (2011) andRodríguez-Caballero et al (2013) describing lichens as runoff promoters and mosses as infiltration promoters for arid ecosystems, but may contradict results of Drahorad et al (2013b) describing a negative relation of infiltration rate and a positive relation of WR with successional stages of moss dominated BSCs under humid climate conditions. Here, vegetation (coniferous trees) plays an important role in the development of WR (Lichner et al, 2007), but this can be ruled out in the Negev desert since there is no sufficient plant cover present that may contribute significantly to WR development.…”
Section: Resultssupporting
confidence: 55%
See 4 more Smart Citations
“…This agrees with Eldridge et al (2010), Maestre et al (2011) andRodríguez-Caballero et al (2013) describing lichens as runoff promoters and mosses as infiltration promoters for arid ecosystems, but may contradict results of Drahorad et al (2013b) describing a negative relation of infiltration rate and a positive relation of WR with successional stages of moss dominated BSCs under humid climate conditions. Here, vegetation (coniferous trees) plays an important role in the development of WR (Lichner et al, 2007), but this can be ruled out in the Negev desert since there is no sufficient plant cover present that may contribute significantly to WR development.…”
Section: Resultssupporting
confidence: 55%
“…Compared to other values of RI measurements from BSCs around the world, ranging from a RI of 4.4 to 210 (cf. Drahorad et al, 2013b;Fischer et al, 2010;Lichner et al, 2013Lichner et al, , 2007) the values measured for the crust in the NW Negev are located in the lower RI range with the highest RI values on wet crust in N84 of 5.70 (see Table 2). The comparison of the RIs between the three sites showed that WR is significantly higher in N84 compared to NS and N69 (p < 0.05).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations